Une culture diplomatique de la frontière dans les Andes (années 1930-années 1950) - François Bignon (Caravelle)
The actors involved in border negotiations between Peru and Ecuador developed a common diplomatic culture which finally led them to a situation of gridlock. Born of the culture of Andean elites, it was rooted in an Iberian heritage, while at the same time claiming a Latin character, as opposed to a pragmatic approach to the border associated with “Anglo-Saxon” conceptions. It was this latter approach which was finally adopted for strategic reasons by the regional powers in the 1942 border treaty, temporarily overcoming the inertia of their traditional diplomatic culture.